The Role of Virtual Try-On Augmented Reality of Cosmetic Products on Purchase Intention Mediated by Brand Trust - Salma Dhianita; Popy Rufaidah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study investigates the impact of Augmented Reality (AR) features, particularly Virtual Try-On (VTO), on purchase intention through brand trust in the context of cosmetic products in Indonesia. The research uses a quantitative approach with a sample of 274 respondents from various cities and provinces in Indonesia. Data analysis was conducted using SmartPLS 3 software, which shows a positive influence of AR on purchase intention mediated by brand trust. The findings indicate that AR Content Quality and AR Service Quality positively affect purchase intention through brand trust. This study provides valuable insights for the cosmetic industry in Indonesia, emphasizing the importance of AR features in enhancing consumer purchase intentions and brand trust. The research highlights that the effective implementation of AR can be a successful strategy for cosmetic companies to increase consumer engagement and loyalty, and drive market growth through technological innovation that aligns with current consumer needs and preferences.